?pm Statistical Convergence of Order ? - Karakas, Abdulkadir; Altin, Yavuz; Et, Mikail (Univ Nis, Fac Sci Math, 2018)
In this work, we generalize the concepts of statistically convergent sequence of order alpha and statistical Cauchy sequence of order alpha by using the generalized difference operator Delta(m). We prove that a sequence is Delta(m)(p)-statistically convergent of order alpha if and only if it is Delta(m)(p)-statistically Cauchy of order alpha.
2nd International Conference on Advances in Natural and Applied Sciences (ICANAS) -- APR 18-21, 2017 -- Antalya, TURKEY
Keywords: Statistical convergence; difference sequence